Comprehensive Physiology 2015
DOI: 10.1002/cphy.c140047
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation: Mechanisms, Therapeutics, and Future Directions

Abstract: Atrial fibrillation (AF) is the most prevalent cardiac arrhythmia, affecting 1% to 2% of the general population. It is characterized by rapid and disorganized atrial activation leading to impaired atrial function, which can be diagnosed on an EKG by lack of a P-wave and irregular QRS complexes. AF is associated with increased morbidity and mortality and is a risk factor for embolic stroke and worsening heart failure. Current research on AF support and explore the hypothesis that initiation and maintenance of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 279 publications
(306 reference statements)
0
86
0
3
Order By: Relevance
“…Atrial fibrillation (AF) is the most common cardiac arrhythmia reported in clinical practice (1). There are three predominant mechanisms underlying AF: Electrical remodeling, structural remodeling and autonomic nerve remodeling (2). It is generally recognized that autonomic nerve remodeling serves an important role in the induction and maintenance of atrial tachycardia and AF (3).…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common cardiac arrhythmia reported in clinical practice (1). There are three predominant mechanisms underlying AF: Electrical remodeling, structural remodeling and autonomic nerve remodeling (2). It is generally recognized that autonomic nerve remodeling serves an important role in the induction and maintenance of atrial tachycardia and AF (3).…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common cardiac arrhythmia, affecting 1 to 2% of the population, and about 8% of individuals over 80 years of age (1). It is characterised by rapid and disorganised heart beating, triggered by electrical impulses usually originating in the roots of the pulmonary veins in the left atrium (LA), and has been identified as the leading cause of thromboembolic events, such as stroke and vascular dementia (2).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding atrial extracellular matrix gene expression, TGF-β1 was similar between groups. TGFβ1 is an established positive regulator of cardiac brosis [27], is upregulated in AF patients with mitral valve disease submitted to valve replacement, and [28] postoperative AF in patients submitted to myocardial revascularization [29]. Nevertheless, studies on aortic stenosis are scarce.…”
Section: Discussionmentioning
confidence: 99%